Large scale analytics of global and regional MOOC providers: Differences in learners' demographics, preferences, and perceptions. (April 2022) - Ruipérez-Valiente, José A.; Staubitz, Thomas; Jenner, Matt; Halawa, Sherif; Zhang, Jiayin; Despujol, Ignacio; Maldonado-Mahauad, Jorge; Montoro, German; Peffer, Melanie; Rohloff, Tobias; Lane, Jenny; Turro, Carlos; et al.
Abstract: Massive Open Online Courses (MOOCs) remarkably attracted global media attention, but the spotlight has been concentrated on a handful of English-language providers. While Coursera, edX, Udacity, and FutureLearn received most of the attention and scrutiny, an entirely new ecosystem of local MOOC providers was growing in parallel. This ecosystem is harder to study than the major players: they are spread around the world, have less staff devoted to maintaining research data, and operate in multiple languages with university and corporate regional partners. To better understand how online learning opportunities are expanding through this regional MOOC ecosystem, we created a research partnership among 15 different MOOC providers from nine countries. We gathered data from over eight million learners in six thousand MOOCs, and we conducted a large-scale survey with more than 10 thousand participants. From our analysis, we argue that these regional providers may be better positioned to meet the goals of expanding access to higher education in their regions than the better-known global providers. To make this claim we highlight three trends: first, regional providers attract a larger local population with more inclusive demographic profiles; second, students predominantly choose their courses based on topical interest, and regional providers do a better job at catering to those needs; and third, many students feel more at ease learning from institutions they already know and have references from. Our work raises the importance of local education in the global MOOC ecosystem, while calling for additional research and conversations across the diversity of MOOC providers. Highlights: MOOC research has understudied the role and trends of regional MOOC providers. We perform a large-scale study with 15 different MOOC providers and more than eight million learners. Regional MOOC providers attract larger local populations, with more inclusive demographic profiles. Regional MOOC providers might be better positioned to fulfil learners' needs.